Functional Metagenomics: A High Throughput Screening Method to Decipher Microbiota-Driven NF-κB Modulation in the Human Gut - Lakhdari, Omar; Cultrone, Antonietta; Tap, Julien; Gloux, Karine; Bernard, Françoise; Ehrlich, S. Dusko; Lefèvre, Fabrice; Doré, Joël; Blottière, Hervé M. (PLOS ONE, 2010)
Background/Aim The human intestinal microbiota plays an important role in modulation of mucosal immune responses. To study interactions between intestinal epithelial cells (IECs) and commensal bacteria, a functional metagenomic approach was developed. One interest of metagenomics is to provide access to genomes of uncultured microbes. We aimed at identifying bacterial genes involved in regulation of NF-κB signaling in IECs. A high throughput cell-based screening assay allowing rapid detection of NF-κB modulation in IECs was established using the reporter-gene strategy to screen metagenomic libraries issued from the human intestinal microbiota. Methods A plasmid containing the secreted alkaline phosphatase (SEAP) gene under the control of NF-κB binding elements was stably transfected in HT-29 cells. The reporter clone HT-29/kb-seap-25 was selected and characterized. Then, a first screening of a metagenomic library from Crohn's disease patients was performed to identify NF-κB modulating clones. Furthermore, genes potentially involved in the effect of one stimulatory metagenomic clone were determined by sequence analysis associated to mutagenesis by transposition. Results The two proinflammatory cytokines, TNF-α and IL-1β, were able to activate the reporter system, translating the activation of the NF-κB signaling pathway and NF-κB inhibitors, BAY 11-7082, caffeic acid phenethyl ester and MG132 were efficient. A screening of 2640 metagenomic clones led to the identification of 171 modulating clones. Among them, one stimulatory metagenomic clone, 52B7, was further characterized. Sequence analysis revealed that its metagenomic DNA insert might belong to a new Bacteroides strain and we identified 2 loci encoding an ABC transport system and a putative lipoprotein potentially involved in 52B7 effect on NF-κB. Conclusions We have established a robust high throughput screening assay for metagenomic libraries derived from the human intestinal microbiota to study bacteria-driven NF-κB regulation. This opens a strategic path toward the identification of bacterial strains and molecular patterns presenting a potential therapeutic interest.